An Untargeted Metabolomic Study of the Effects of Vitamin D and/or Calcium Supplementation Among Individuals at High Risk for Colorectal Neoplasms. (29th May 2020) - Nesbeth, Paula-Dene; Fedirko, Veronika; Jones, Dean; Yu, Tianwei; Bostick, Roberd; Barry, Elizabeth; Baron, John
Abstract: Objectives: To obtain preliminary data on the independent and synergistic anti-neoplastic effects of 1-year supplementation with vitamin D3 and/or calcium on the plasma metabolome and metabolic pathways among individuals at high risk for colorectal neoplasms. Methods: This study was an untargeted metabolomic analysis that used data and biosamples from a completed, large, multicenter, randomized, placebo-controlled, clinical trial of vitamin D3 (1000 IU/d) and/or calcium (1200 mg/d via calcium carbonate) for preventing colorectal adenoma recurrence. High resolution liquid chromatography-mass spectrometry with positive and negative ion modes was used to measure >20, 000 metabolites in the baseline and year 1 follow-up plasma samples from the four treatment groups (n = 30/group).  The data were processed for peak extraction and quantification of ion intensities using xMSanalyzer software with apLCMS. Using repeated measures mixed models and false discovery rate adjustment, top features associated with each treatment combination were identified. Significant features (unadjusted P <   0.05) were analyzed in mummichog 2.0 to identify enriched metabolic pathways associated with each treatment agent. Results: Following 1 year of treatment, in the calcium treatment group relative to placebo, pathways related to carnitine shuttle; prostaglandin formation from arachidonate; fructose and caffeine metabolism were significantly modulated ( P < 0.05). Prostaglandin formation from arachidonate; carnitine shuttle; N-glycan and keratan sulfate degradation were significantly associated with calcium plus vitamin D3 treatment ( P < 0.05). Metabolic pathways significantly modulated with vitamin D3  treatment were leukotriene, vitamin D3, vitamin E, vitamin A, arachidonic acid metabolism, and fatty acid activation ( P < 0.05). Conclusions: Our preliminary results suggest significant changes in prostaglandin formation pathway in plasma of individuals at high risk for colorectal cancer supplemented for 1 year with calcium alone and calcium plus vitamin D3 . Vitamin D3 supplementation modulated the arachidonic acid pathway supporting its effects on inflammation. Our study supports continued investigation of vitamin D3 and calcium's anti-carcinogenic actions. Funding Sources: National Cancer Institute.